FUNCTIONALITY AND PERFORMANCE OF THE GIRL CHILD STUDENT TRANSPORTATION PROGRAM IN KANO METROPOLIS - Suleiman, D.; Iliyasu, I. S. (FUDMA JOURNAL OF SCIENCES, 2021)
This study evaluates the performance of the Girl Child Student Transportation Program in Kano Metropolis. Data used for this study was obtained through questionnaire administration to the passengers that patronized the Girl Child Student Transportation Program. Purposive sampling technique was employed in the selection of respondents and 235 copies of questionnaire were administered to the respondents and 223 were retrieved and used in the data analysis. The study employed the use of both descriptive and inferential statistical methods of data analysis. The findings showed that 62 (53.9%) of the buses are used for the program are fully functional, 29 (25.2%) of the buses are partially functional and 24 (20.9%) of the buses are grounded. The result of the linear regression analysis revealed with inferential evidence that, only seating capacity has a significant relationship with the patrons’ trip frequency out of the various service quality determinants. The paper recommends that the management of the Girl child student transportation program needs to design a frame work that will guide the seating arrangement of the bus service in order to achieve the desire goal of the program
Keywords: Students’ Transportation, Academic Performance, Public Schools, Bus Service, Reliability of Operation